Prenatal diagnosis by trio exome sequencing in fetuses with ultrasound anomalies: A powerful diagnostic tool - Tran Mau-Them, Frédéric; Delanne, Julian; Denommé-Pichon, Anne-Sophie; Safraou, Hana; Bruel, Ange-Line; Vitobello, Antonio; Garde, Aurore; Nambot, Sophie; Bourgon, Nicolas; Racine, Caroline; Sorlin, Arthur; Moutton, Sébastien; et al. (Frontiers in Genetics, 2023)
Introduction: Prenatal ultrasound (US) anomalies are detected in around 5%–10% of pregnancies. In prenatal diagnosis, exome sequencing (ES) diagnostic yield ranges from 6% to 80% depending on the inclusion criteria. We describe the first French national multicenter pilot study aiming to implement ES in prenatal diagnosis following the detection of anomalies on US. Patients and methods: We prospectively performed prenatal trio-ES in 150 fetuses with at least two US anomalies or one US anomaly known to be frequently linked to a genetic disorder. Trio-ES was only performed if the results could influence pregnancy management. Chromosomal microarray (CMA) was performed before or in parallel. Results: A causal diagnosis was identified in 52/150 fetuses (34%) with a median time to diagnosis of 28 days, which rose to 56/150 fetuses (37%) after additional investigation. Sporadic occurrences were identified in 34/56 (60%) fetuses and unfavorable vital and/or neurodevelopmental prognosis was made in 13/56 (24%) fetuses. The overall diagnostic yield was 41% (37/89) with first-line trio-ES versus 31% (19/61) after normal CMA. Trio-ES and CMA were systematically concordant for identification of pathogenic CNV. Conclusion: Trio-ES provided a substantial prenatal diagnostic yield, similar to postnatal diagnosis with a median turnaround of approximately 1 month, supporting its routine implementation during the detection of prenatal US anomalies.